Transformational Leadership Dan Pengaruhnya Terhadap Peningkatan Efisiensi Dan Produktivitas Pegawai Di Sekretariat DPRD Kota Medan - Ramadhani, Sri; Aprinilova Barus, Vivi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This study aims to analyze the effect of transformational leadership on improving employee efficiency and productivity at the Medan City DPRD Secretariat. The method used was descriptive qualitative analysis, focusing on relevant documents, including employee performance reports, organizational policies, and meeting notes. The data obtained from these documents provided insight into the leadership practices implemented and their impact on employee performance. The results showed that transformational leadership plays an important role in improving employee efficiency and productivity. Document analysis revealed that leaders who applied this leadership style succeeded in creating a supportive work environment, increasing employee motivation, and strengthening commitment to organizational goals. In addition, documents also show an increase in employee performance in line with the application of transformational leadership principles. The findings provide strategic implications for management development at the Medan City DPRD Secretariat, emphasizing the importance of applying transformational leadership to achieve better results in employee performance. Therefore, it is recommended that leaders in this environment continue to develop inspirational and supportive leadership styles.